Trends in digital library research : a knowledge mapping and ontology engineering approach. - Son Hoang Nguyen (2015)
Mapping digital library research is very helpful for digital library research and education communities to have a knowledge platform to guide, evaluate, and improve the activities of digital library research, education and transforming it into a digital library ontology for various applications. However, so far, there has not been any research on mapping digital library research for serving such purposes.